ANALISA EARNING PER SHARE (EPS) DAN DEBT TO EQUITY RATIO (DER) IMPLIKASINYA TERHADAP HARGA SAHAM PT. BANK NEGARA INDONESIA (PERSERO) TBK. PERIODE 2012-2021 - Eman Singgih (Journal Of Communication Education, 2022)
ABSTRACTThis study aims to determine the effect of Earning Per Share (EPS) and Debt to Equity Ratio (DER) on the stock price of PT. Bank Negara Indonesia (Persero) Tbk, Period 2012-2021 partially or simultaneously. This research was conducted on the Jakarta Indonesia Stock Exchange from May 2022 to August 2022. The population in this study is the financial statements of PT. Bank Negara Indonesia (Persero) Tbk, which is listed on the Indonesia Stock Exchange (IDX). The sample in this study is a list of financial statements at PT. Bank Negara Indonesia (Persero) Tbk. While the sampling method used purposive sampling. The data analysis technique used is simple and multiple linear regression, for hypothesis testing using t test and f test with a significance level of 5%. Calculations were carried out using the SPSS (Statistical Product and Service Solution) application tool version 22. Based on the results of data analysis, the Earning Per Share variable partially has a significant effect on the Stock Price. The variable Debt to Equity Ratio partially has no significant effect on stock prices. And simultaneously the Earning Per Share and Debt to Equity Ratio variables have a significant influence on the Stock Price.Keywords: Earnings Per Share, Debt to Equity Ratio and Stock Price